TURNOVER INTENTION DITINJAU DARI JOB EMBEDEDDNESS PADA KARYAWAN BAGIAN PRODUKSI PT. EXPRAVET NASUBA MEDAN - Vinesa Intan Savira (Psikologi Prima, 2018)
This study aims to determine the relationship between job embededdness and turnover intention. The subjects of this were 102 employees of production in PT. Expravet Nasuba Medan. Data were obtained from scales to measure job embededdness and turnover intention. The data is analyzed by Product Moment correlation through SPSS 18 for Windows. The result shows that there is a negative relationship between job embededdness and turnover intention, with correlation coefficient r = -0.571 and (p < 0.05). Based on the results, it is concluded that the hypothesis is acceptable, and there is a negative correlation between job embededdness and turnover intention.